1994
DOI: 10.1002/1097-0142(19940615)73:12<3047::aid-cncr2820731225>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Use of positron emission tomography with fluorodeoxyglucose in patients with extracranial head and neck cancers

Abstract: Background. The purpose of this study was to evaluate the utility of positron emission tomography‐ (PET) 2‐[18F]‐fluoro‐2‐deoxy‐D‐glucose (FDG) imaging in extra‐cranial head and neck cancers. Methods. Sixty patients with biopsy‐proven cancers were studied using PET‐FDG. Thirty‐four patients were studied before therapy (staging), of which 15 patients received primary radiotherapy and serial PET‐FDG imaging (monitoring). Seven patients with advanced disease had laser excision (monitoring), and 19 patients were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
81
1
8

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(94 citation statements)
references
References 7 publications
4
81
1
8
Order By: Relevance
“…It has been applied to staging and surveillance of patients with head and neck SCC (Rege et al, 1994;Braams et al, 1995), but a more promising observation is that high FDG uptake in head and neck SCC is associated with poor survival (Minn et al, 1997). A similar association has also been demonstrated for other malignancies such as brain, lung and malignant lymphomas (Patronas et al, 1985;Okada et al, 1992;Ahuja et al, 1998), where it appears that the prognostic value of a high SUV may act independently of tumour stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been applied to staging and surveillance of patients with head and neck SCC (Rege et al, 1994;Braams et al, 1995), but a more promising observation is that high FDG uptake in head and neck SCC is associated with poor survival (Minn et al, 1997). A similar association has also been demonstrated for other malignancies such as brain, lung and malignant lymphomas (Patronas et al, 1985;Okada et al, 1992;Ahuja et al, 1998), where it appears that the prognostic value of a high SUV may act independently of tumour stage.…”
Section: Discussionmentioning
confidence: 99%
“…FDG -PET has already been applied to staging and follow-up of patients with head and neck cancer (Rege et al, 1994;Braams et al, 1995), and Minn et al (1997) have shown that high uptake as determined by the standardized uptake value (SUV) was associated with poor survival. However it is not clear whether a high SUV simply reflects the stage of disease or is an independent predictor of survival.…”
mentioning
confidence: 99%
“…They can also indicate uptake and involvement of normal size lymph nodes while showing no involvement in some enlarged reactive lymph nodes. Evaluation of the accuracy of FDG PET in the diagnosis of the primary tumour has been performed to validate its potential in this type of tumour rather than to support its clinical use in this indication [206][207][208][209]. Minn et al were able to image 13/13 cancers using FDG [202].…”
Section: Head and Neck Carcinomasmentioning
confidence: 99%
“…18 F-FDG PET offers a tool that enables the early detection of HNSCC recurrences. 18 F-FDG PET can distinguish recurrent HNSCC from posttreatment changes and is more effective in detecting recurrent tumors than physical examination, CT, or MRI (8)(9)(10)(11)(12)(13). However, in most of these studies, the objective was to assess the ability of 18 F-FDG PET to visualize a recurrence that was clinically already highly suspected.…”
mentioning
confidence: 99%